From Profiling to Management: A Systematic Review of The Prevalence, Clinical Profile, and Outcomes in Isolated Systolic Hypertension - Syawaliyah, Ainun Ni'mah; Khairunnisa, Naura Alifa (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2025)
Introduction: Isolated Systolic Hypertension (ISH) is a type of hypertension that was initially found mostly in the elderly, although recent studies indicate that it is increasingly common in younger adults. ISH has clinical implications for cardiovascular health and target organs. Limited awareness and management of ISH highlight the urgency of comprehensive studies to deepen understanding. Method: This study is a systematic review conducted in accordance with the PRISMA 2020 guidelines. Literature was searched from the PubMed, Scopus, and Web of Science databases. Included articles were primary studies with cross-sectional, cohort, RCT, or primary meta-analysis designs published between 2016 and 2025, in English, and available in open access. Risk of bias assessment was conducted using the RoB 2 tool and the Newcastle-Ottawa Scale. Discussion: A total of 24 articles met the inclusion criteria, covering more than 4 million participants from various age groups. Epidemiological studies indicate a high prevalence of ISH, even among adolescents and young adults. The main risk factors include age, high BMI, insulin resistance, low physical activity, and socioeconomic factors. ISH is associated with various clinical conditions, such as increased left ventricular mass, arterial stiffness, and impaired kidney function. Pharmacological interventions like calcium channel blockers and beta-blockers show varying effectiveness. Non-pharmacological approaches, such as renal denervation, have limited effects on pure ISH. Conclusion: ISH is a high-risk condition that is widespread across various age groups. Understanding its epidemiology, risk factors, pathophysiology, and response to treatment is important for appropriate therapy and prevention of long-term clinical implications.